Managed retreat in response to flooding: lessons from the past for contemporary climate change adaptation. (2nd November 2021) - Tubridy, Fiadh; Scott, Mark; Lennon, Mick
ABSTRACT: Managed retreat is increasingly advocated as a means to promote resilience and adaptation to climate change. However, there are various uncertainties and challenges associated with the impacts of displacement and attachments to place. In this context, it is useful to study past examples of relocation to understand how these challenges have been addressed. This paper draws on a case study relocation scheme which took place in Ireland following major flooding in 1954. This represented a radical and comprehensive approach to relocation which sought to address the root causes of vulnerability. The analysis shows that this comprehensive approach was made possible through a connection between managed retreat and land reform. The scheme also faced opposition linked to attachments to place and property. This led to compromises and a failure to fully address the effects of flooding on livelihoods but contributed to resilience through ensuring that family and community ties remained intact. The paper's distinctive contributions are its analysis of the requirements of transformative approaches to adaptation and relocation, its identification of challenges associated with place and property even in the context of such transformative approaches, and its adding of historical depth to contemporary debates on climate adaptation.